Radical Group Degradation Study of Linear Low Density Polyethylene for Developing Environmentally Degradable Plastic Bags (Journal of Chemical Engineering, 2013)
We study the influence of adding three different type of additives on film grade polyethylene on the degradation behavior under natural weathering conditions in Saudi Arabia. Plastic films prepared by first premixing the film grade polyethylene pellets with different amounts of additives were exposed in outdoor environments located in Dhahran, Saudi Arabia. Original and degraded polymeric materials, as well as the relevant extractable fractions were characterized by FTIR. Carbonyl and double bond indexes were calculated on the basis of the relative intensities of the carbonyl band at 1715 cm-1 and the double-bond band at 1650 cm-1 to that of methylene scissoring band at 1465 cm-1, respectively. Comparison of different additives on the basis of degradation rate was determined and the additive PDQ shows the highest degradation rate at the amount of 10% mixing with Polyethylene. DOI: http://dx.doi.org/10.3329/jce.v27i1.15863 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 74-77